Transmission efficiency and noise, vibration and harshness refinement of differential hypoid gear pairs. (March 2014) - Mohammadpour, M; Theodossiades, S; Rahnejat, H; Kelly, P
This article presents a combined multi-body dynamics and lubricated contact mechanics model of vehicular differential hypoid gear pairs, demonstrating the transient nature of transmission efficiency and noise, vibration and harshness performance under various driving conditions. The contact of differential hypoid gears is subjected to mixed thermo-elastohydrodynamic regime of lubrication. The coefficient of friction is obtained using an analytical approach for non-Newtonian lubricant shear and supplemented by boundary interactions for thin films. Additionally, road data and aerodynamic effects are used in the form of resisting torque applied to the output side of the gear pair. Sinusoidal engine torque variation is also included to represent engine order torsional input resident on the pinion gear. Analysis results are presented for New European Driving Cycle transience from low-speed city driving condition in second gear to steady-state cruising in fourth gear for a light truck. It is shown that the New European Driving Cycle captures the transmission efficiency characteristics of the differential hypoid gear pair under worst case scenario, with its underlying implications for fuel efficiency and emissions. However, it fails to address the other key attribute, being the noise, vibration and harshness performance. In the case of hypoid gears, the resultant noise, vibration and harshness characteristics can be particularly annoying. It is concluded that broader transient manoeuvres encompassing New European Driving Cycle are required for assessment, in order to obtain a balanced approach for transmission efficiency and noise, vibration and harshness performance. This approach is undertaken in this article, which is not hitherto reported in the literature.